(untitled) (Medicine Anthropology Theory, 2017)
The private space of the home is an important site of health care in most industrialised countries, and rehabilitation following intensive in-hospital treatment largely takes place in domestic settings. Home in this context is implicitly understood by individuals affected by illness (people with illness, family members, friends, carers), health care providers, and policy makers as an a priori entity that naturally provides continuity and stability. This takes for granted that family carers will maintain both therapeutic activities and the sense of ‘being at home’ – and all of the accompanying emotional dimensions – within the home environment. Drawing on ethnographic research with relatively young spousal carers in Victoria, Australia, we explore how the reconstruction of home as a site for post-stroke recovery changed the experiences and meanings given to the idea of home. Home as a therapeutic place depended on constant orchestrating work that reconfigured the physical, symbolic, and practical elements of home. This was not a straightforward or singular process, as tensions arose in trying to integrate the new, post-stroke therapeutic landscape and pre-stroke conceptualisations and lived realities of home life.